Effective strategies in technical writing - Abelos, Alex V.; Avila, Dorcas M.; Imson, Maria Elinora P.; Asperas, Matilde A.; Viar, Orlando M.; Reyes, Yolanda D. (Cabanatuan City : Jimcy Publishing House, 2005)
The textbook itself is the centerpiece of a comprehensive teaching and learning package that targets a single goal: to successfully demonstrate how trade and technical jargons works in the real world, thus helping students to understand the concepts behind effective communication and to develop and refine their own skills in the technical profession.
Chapter 2 An introduction to technical writing -- Chapter 2 Technical writing process/ producing the product -- Chapter 3 Objectives in technical writing -- Chapter 4 Audience recognition and involvement -- Chapter 5 Technical writing correspondence -- Chapter 6 Technical writing correspondence/letters -- Chapter 7 The job search and letter of application -- Chapter 8 Technical reports -- Chapter 9 Writing technical proposals -- Chapter 10 Technical description -- Chapter 11 The use of graphics in technical writing.
Keywords: ENGLISH LANGUAGE -- TECHNICAL ENGLISH -- PROBLEMS, EXERCISES, ETC; COMMUNICATION OF TECHNICAL INFORMATION -- PROBLEMS, EXERCISES, ETC; TECHNICAL WRITING -- PROBLEMS, EXERCISES, ETC